A Novel TetR Family Transcriptional Regulator, CalR3, Negatively Controls Calcimycin Biosynthesis in Streptomyces chartreusis NRRL 3882 - Gou, Lixia; Han, Tiesheng; Wang, Xiaoxia; Ge, Jingxuan; Liu, Wenxiu; Hu, Fen; Wang, Zhijun (Frontiers in Microbiology, 2017)
Calcimycin is a unique ionophoric antibiotic that is widely used in biochemical and pharmaceutical applications, but the genetic basis underlying the regulatory mechanisms of calcimycin biosynthesis are unclear. Here, we identified the calR3 gene, which encodes a novel TetR family transcriptional regulator and exerts a negative effect on calcimycin biosynthesis. Disruption of calR3 in Streptomyces chartreusis NRRL 3882 led to significantly increased calcimycin and its intermediate cezomycin. Gene expression analysis showed that the transcription of calR3 and its adjacent calT gene were dramatically enhanced (30- and 171-fold, respectively) in GLX26 (ΔcalR3) mutants compared with the wild-type strains. Two CalR3-binding sites within the bidirectional calR3-calT promoter region were identified using a DNase I footprinting assay, indicating that CalR3 directly repressed the transcription of its own gene and the calT gene. In vitro electrophoretic mobility shift assays suggested that both calcimycin and cezomycin can act as CalR3 ligands to induce CalR3 to dissociate from its binding sites. These findings indicate negative feedback for the regulation of CalR3 in calcimycin biosynthesis and suggest that calcimycin production can be improved by manipulating its biosynthetic machinery.